Prostorski informacijski sistem v programu CAMP Slovenija - Maher, Igor (Urbani izziv, 2005)
Today spatial data is directly or indirectly dealt with by states, local communities, companies, numerous government and non-government organisations, societies and other informal groups. The publics demand to be informed and have to be informed about spatial occurrences in their living environment, which projects and activities are underway and subsequently voice their opinions and act to affect quality improvements in space. Information tied to space and physical projects is dispersed. Even efficient interchange of information between government and municipal authority is not practised. Spatial planning is a multi-disciplinary activity, with numerous participatingdisciplines and levels. Successful activity in physical planning needs efficient cooperation between all responsible parties involved in physical planning - the state and local communities, independent governmental departments and the local communities themselves. Exchange of information is crucial for the process of physical planning, but can be enabled only with a good system for information gathering and delivery.
Keywords: informacijski sistemi; prostorski podatki; prostorsko planiranje; prostorsko urejanje; spatial planning